Alcohol-Attributable Medical Costs in Commercially Insured and Medicaid Populations - Pelin Ozluk, PhD; Rebecca Cobb, MS; Gosia Sylwestrzak, MA; Dheeraj Raina, MD; Eric Bailly, MA (Elsevier, 2022)
Introduction: Despite its social acceptance, excessive alcohol use remains among the top causes of preventable deaths in the U.S. Although there is a recognition of alcohol-related health and social costs, there are no current studies quantifying the medical costs incurred under health plans. Methods: This study estimates the direct medical costs attributable to excessive alcohol use using claims records from a large national insurer. The sample consists of adults with commercial insurance and Medicaid between 2008 and 2019. A case-control matched study design is used to compare individuals with a condition considered 100% attributable to alcohol by the Centers for Disease Control and Prevention with similar individuals. Medical care use and costs are examined over a 12-month follow-up. Costs are broken down by healthcare setting and health conditions as defined by the Centers for Disease Control and Prevention's Alcohol-Related Disease Impact diagnoses codes. Results: We find that having a diagnosis attributable to alcohol is associated with higher annual per-person healthcare expenditures in both commercially insured and Medicaid-insured participants by $14,918 (95% CI=$14,540, $15,297) and $4,823 (95% CI=$4,489, $5,158), respectively. We find that 60%‒75% of the additional costs of excessive alcohol use are driven by heart disease and stroke; conditions of the liver, gallbladder, and pancreas; and certain cancers as well as acute conditions that may be attributable to alcohol. Conclusions: The findings suggest that public and private initiatives to target people vulnerable to the harms of excessive alcohol use may potentially help to cut down significant costs on the already strained healthcare system in the U.S.